Preparation and Charactrization of 1,3- dipolar cycloaddition of nitrones with but-2-ynedioic acid - Raad.J.Ali (University of Thi-Qar Journal, 2019)
Some nitrones(1-3), derived from N-p-tolylhydroxylamine with substituted benzaldehyde such as(4-Chlorobenzaldehyde,4-Florobenzaldehyde, 4-Nitrobenzaldehyde ) .Ther reaction with but-2-ynedioic acid include 1,3- dipolar cycloaddition reaction to give isoxazoles (4-6),They have been identified by 1HNMR, IR and Mass spectra